1974
DOI: 10.1111/j.1423-0410.1974.tb02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement‐Fixing and Lymphocytotoxic Antibodies in Serum of Pregnant Women at Delivery

Abstract: Data from an examination of 2,008 sera from parous women for lymphocytotoxic antibodies (LCTAb) and complement-fixing platelet antibodies (CFPAb) are presented. The incidence of LCTAb was 13.4% and the incidence of CFPAb 2.9%. The finding of 14 sera with CFPAb to platelets in the absence of LCTAb is discussed. It is suggested that cytotoxic antibodies belong to two different globulin classes: complementfixing cytolytic antibodies and blocking antibodies only cytolytic with rabbit complement. The incidences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Like other authors [Goodman and Masaitis, 1967;Ahrons, 1971;Heinrich et al, 1973;Nymand, 1969;Décary et al, 1984], we found that the sera of female patients contained a greater diversity of alloantibodies than those of male patients, which can be explained by the additional immunizing in fluence of pregnancy. In fact, all the female patients whose sera were tested had been pregnant (table I).…”
Section: Discussionsupporting
confidence: 87%
“…Like other authors [Goodman and Masaitis, 1967;Ahrons, 1971;Heinrich et al, 1973;Nymand, 1969;Décary et al, 1984], we found that the sera of female patients contained a greater diversity of alloantibodies than those of male patients, which can be explained by the additional immunizing in fluence of pregnancy. In fact, all the female patients whose sera were tested had been pregnant (table I).…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, maternal immunization during pregnancy is found less frequently than expected [8]. In addition to other factors, this observation could be explained by the existence of cross-reacting antigens in the HL-A system, in that, with a few exceptions [6,16], antigens do not challenge an individual who possesses cross-reacting antigens to the chal lenge [6].…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand it should be kept in mind that the cause of undetectable LCTAb at delivery could be a consequence of antigen-bound LCTAb, which may have a blocking effect during pregnancy [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations